What predicts sex partner age differences among African American youth? A longitudinal study from adolescence to young adulthood - Bauermeister, José A. (2010)
Partner age is associated with youth’s sex risk behaviors and sexually transmitted infections. At present, however, we do not know whether the co-occurrence of other risk behaviors is associated with having older sex partners during adolescence and young adulthood. Using growth curve modeling, we first described the shape of the age difference between participants and their sex partners across adolescence and young adulthood in a sample of African American youth. Second, we tested whether this model varied systematically by sex, mother’s education, and high school dropout. Third, we assessed whether age differences were associated with youth’s self-acceptance, alcohol use, and employment trajectories over these two developmental periods. Finally, we tested whether these associations had non-proportional effects over both periods. We modeled sex partners’ age differences non-linearly, with females being more likely to date older partners at baseline and over time. High school dropouts also reported older partners at baseline. Self-acceptance and the number of hours worked were associated with sex partners’ age differences over time, with the effect decreasing over young adulthood years. Alcohol use frequency was also associated with having older partners over time. We discuss the findings from a health perspective on youth’s sexual development.